Education Amid COVID-19 Pandemic : Understanding the Response of Poor and Marginalised in Kashmir - Ganayee, Shameem Ahmad; Gadda, Zakir Hussain; Jahangir, Mohamad Saleem (JOURNAL OF INDIAN EDUCATION, 2023)
Using a qualitative approach, the present study aimed to explore the response of the poor and marginalised, particularly the Mid-day Meal (MDM) beneficiaries to online education, thrusted untimely by the unprecedented COVID-19 pandemic in Kashmir (India). Based primarily on the experiences of 28 participants belonging to various areas of Kashmir, the data was collected using face-to-face semi structured interviews. The results of the study revealed that the sudden shift to online education amid COVID-19 has augmented the marginalisation of poor students, thereby exposing them to a more severe educational disadvantage. It is generally due to the inaccessibility, and unawareness of ICT-enabled gadgets among them. Hence, this digital marginality needs to be addressed, to bring underprivileged children into the fold of digital education.